Novel low viscosity ammonium-based ionic liquids with carboxylate anions: Synthesis, characterization, and thermophysical properties - Al Kaisy, G.M.J. (Elsevier B.V., 2017)
A new group of low viscosity hydrophobic trioctylammonium-based protic ionic liquids (PILs) with 2-naphthoate, 4-tert-butylbenzoate, 2-hexyldecanoate, and 4-phenylbutanoate anions were synthesized. All the synthesized PILs were liquids at room temperature. The PILs were characterized using nuclear magnetic resonance, elemental analysis, and Fourier transform infrared spectroscopy. Thermogravimetric analysis was conducted to determine the decomposition temperature of the PILs. The PILs were then subjected to thermophysical properties study where their densities, viscosities, refractive indices, and surface tensions were measured within the temperature range of 298.15 to 363.15 K at atmospheric pressure and correlated with established empirical equations. Other thermophysical properties such as molar volume, standard entropy, and lattice potential energy were determined using the measured density data whilst the surface excess energy and entropy were estimated using the measured surface tension data. © 2017 Elsevier B.V.